MAKNA LEKSIKAL DAN GRAMATIKAL: KETIMPANGAN AKSES PENDIDIKAN DALAM MEDIA BERITA WILAYAH TERPENCIL - Sabrina Aulia Firdaus; Beyonda Proudy Sujianto; Intan Feby Putri Yulian; Ingghar Ghupti Nadia Kusmiaji (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study analyzes lexical and grammatical meanings in the news text “Education in Remote Areas: The Government’s Challenge in Equalizing Education in Indonesia” published on the official website of the Secretariat of State of the Republic of Indonesia (setneg.go.id). The purpose of this study is to describe the use of lexical and grammatical meanings and to explain their role in constructing messages about educational inequality in remote areas. This research employs a descriptive qualitative design with a single online news text as the research subject, while the research object consists of words, phrases, and sentences containing lexical and grammatical meanings. Data were collected through documentation and analyzed using identification, classification, and descriptive interpretation based on semantic theory. The findings indicate that lexical meanings are used in a literal and factual manner, while grammatical meanings are formed through affixation and syntactic relationships that clarify the structure and message of the news. These results show that language plays an important role in presenting educational equity issues clearly and systematically.